A newly qualified physiotherapist non-medical prescriber in the pandemic. (2nd June 2021) - Chambers, Hannah
Abstract : Hannah Chambers discusses what it is like to be a new non-medical prescriber within physiotherapy, having to implement and develop new skillls during the COVID-19 pandemic